A Closer Look at Economic Context in Identity Distress, Identity Development, and Adjustment to University. Issue 4 (1st October 2020) - Gfellner, Barbara M.; Cordoba, Ana I.
ABSTRACT: In this study, national rates of youth unemployment were used as a proxy for economic disruption and stability in Spain and Canada, respectively. Identity distress was examined in relation to identity processes, and adjustment to college among university students in these contexts. Students in Spain (N = 95, Mage  = 19.3, (1.6); mdn = 19 years; 86% female) and Canada (N = 331; Mage  = 19.6 (2.2); mdn = 19 years; 82% female) completed the Identity Distress Scale, Dimensions of Identity Development Scale, and Student Adjustment to College Questionnaire. Overall predicted relationships were supported across the variables. As expected, elevated identity distress was found among Spanish students. Economic context moderated relationships between (1) ruminative exploration and academic adjustment and (2) identity distress and personal-emotional adjustment both with a greater magnitude of association for students in the stable economic context, respectively. Moderated mediation showed that context moderated indirect effects of ruminative exploration through identity distress on personal-emotional adjustment. The findings indicated a certain resilience in dealing with the contextual stressor among students in Spain whereas those in the stable economic context appear to conform more closely to a typical progression of identity development. Implications for research and intervention are discussed.